Estimating Spillover Risk Among Large EU Banks - Ong, Li.; Cihak, Martin (Washington, D.C. : International Monetary Fund, 2007)
The paper examines the scope for cross-border spillovers among major EU banks using information contained in the stock prices and financial statements of these banks. The results suggest that spillovers within domestic banking systems generally remain more likely, but the number of significant cross-border links is already larger than the number of significant links among domestic banks, adding a piece of empirical evidence supporting the need for strong cross-border supervisory cooperation within the EU.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet